Two years of post-wildfire impacts on dissolved organic matter, nitrogen, and precursors of disinfection by-products in California stream waters - UZUN, HABİBULLAH (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
We investigated the effects of two California wildfires (Rocky and Wragg Fires, 2015) compared to an unburned reference watershed on water quality, dissolved organic matter (DOM), and precursors of disinfection by-products (DBPs) for two years' post-fire. The two burned watersheds both experienced wildfires but differed in the proportion of burned watershed areas. Burned watersheds showed rapid water quality degradation from elevated levels of turbidity, color, and suspended solids, with greater degradation in the more extensively burned watershed. During the first year's initial flushes, concentrations of dissolved organic carbon (DOC), dissolved organic nitrogen (DON), ammonium (NH4+/NH3), and specific ultraviolet absorbance (SUVA(254)) were significantly higher (67 +/- 40%, 418 +/- 125%, 192 +/- 120%, and 31 +/- 17%, respectively) in the more extensively burned watershed compared to the reference watershed. These elevated values gradually declined and finally returned to levels like the reference watershed in the second year. Nitrate concentrations were near detection limits (0.01 mg-N/L) in the first year but showed a large increase in fire-impacted streams during the second rainy season, possibly due to delayed nitrification. Changes in DOM composition, especially during the initial storm events, indicated that fires can attenuate humic-like and soluble microbial by-product-like (SMP) DOM while increasing the proportion of fulvic-like, tryptophan-like, and tyrosine-like compounds. Elevated bromide (Br-) concentrations (up to 8.7 mu M]) caused a shift in speciation of trihalomethanes (THMs) and haloacetic acids (HAAs) to brominated species for extended periods (up to 2 years). Wildfire also resulted in elevated concentrations of N-nitrosodimethylamine (NDMA) precursors. Such changes in THM, HAA, and NDMA precursors following wildfires pose a potential treatability challenge for drinking water treatment, but the effects are relatively short-term (<= 1 year). (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Wildfires; Drinking water quality; Nitrogen cycle; DOM properties; DBP FPs; POLYCYCLIC AROMATIC-HYDROCARBONS; MATRIX REGIONAL-INTEGRATION; NDMA FORMATION POTENTIALS; DRINKING-WATER; FLUORESCENCE SPECTROSCOPY; QUANTIFY SPECTRA; FOREST-FIRE; SOIL; PHOSPHORUS; DYNAMICS